The hydrolysis of agro-industrial residues by holocellulose-degrading enzymes - Moreira, Leonora Rios de Souza (2012)
Holocellulose structures from agro-industrial residues rely on main and side chain attacking enzymes with different specificities for complete hydrolysis. Combinations of crude enzymatic extracts from different fungal species, including Aspergillus terreus, Aspergillus oryzae, Aspergillus niger and Trichoderma longibrachiatum, were applied to sugar cane bagasse, banana stem and dirty cotton residue to investigate the hydrolysis of holocellulose structures. A. terreus and A. oryzae were the best producers of FPase and xylanase activities. A combination of A. terreus and A. oryzae extracts in a 50% proportion provided optimal hydrolysis of dirty cotton residue and banana stem. For the hydrolysis of sugar cane bagasse, the best results were obtained with samples only containing A. terreus crude extract.